Efficient Periodic Broadcasting for Mobile Networks at Small Client Receiving Bandwidth and Buffering Space - Hsiang-Fu Yu; Yao-Tien Wang; Jong-Yih Kuo; Chu-Yi Chien (Journal of Applied Mathematics)
Periodic broadcasting is an effective approach for delivering popular videos. In general, this approach does not provide interactive (i.e., VCR) functions, and thus a client can tolerate playback latency from a video server. The concept behind the approach is partitioning a video into multiple segments, which are then broadcast across individual communication channels in terms of IP multicast. The method improves system throughput by allowing numerous clients to share the channels. For many broadcasting schemes, client receiving bandwidth must equal server broadcasting bandwidth. This limitation causes these schemes to be infeasible in mobile networks because increasing receiving bandwidth at all client sites is expensive, as well as difficult. To alleviate this problem, the fibonacci broadcasting (FiB) scheme allows a client with only two-channel bandwidth to receive video segments. In comparison with other similar schemes, FiB yields smallest waiting time. Extending FiB, this work proposes a new scheme (called FiB+) to achieve smaller client buffering space and the same waiting time under two-channel receiving bandwidth. Extensive analysis shows that FiB+ can yield 34.5% smaller client buffer size than that of FiB. Further simulation results also indicate that FiB+ requires lower client buffering space than several previous schemes.